Specificities of a chemically modified laccase from trametes hirsuta on soluble and cellulose-bound substrates - Schroeder, M. (2006)
Laccases could prevent fabrics and garments from re-deposition of dyes during washing and finishing processes by degrading the solubilized dye. However, laccase action must be restricted to solubilized dye molecules thereby avoiding decolorization of fabrics. Chemical modification of enzymes can provide a powerful tool to change the adsorption behaviour of enzymes on water insoluble polymers. Polyethylene glycol (PEG) was covalently attached onto a laccase from Trametes hirsuta. Different molecular weights of the synthetic polymer were tested in terms of adsorption behaviour and retained laccase activity. Covalent attachment of PEG onto the laccase resulted in enhanced enzyme stability while with increasing molecular weight of attached PEG the substrate affinity for the laccase conjugate decreased. The activity of the modified laccases on fibre bound dye was drastically reduced decreasing the adsorption of the enzyme on various fabrics. Compared to the 5 kDa PEG laccase conjugate (K/S value 47.60)